SGI Canada Educators' Perspectives on Creating Value in the Teaching and Learning Environment - Sherman, Paul; Boukydis, Olivia (Journal of Social, Humanity, and Education, 2023)
Purpose: The purpose of this study was to examine the perspectives and experiences of educators who practice Soka (value-creating) pedagogy in their teaching and learning environment. Methodology: The participants were educators who were teaching, or had taught, in a formal public or private education system in Canada and were also affiliated with the Soka Gakkai International Association of Canada Educators Group. An online survey was distributed to the educators describing the study and requesting their participation in a semi-structured interview. Fourteen survey respondents were chosen for an interview. Results: The study’s findings revealed important themes concerning how Soka education positively influenced the educators’ relationships with their students, how teachers structured their teaching and learning environment, how teachers perceived their role as educators, and how the teachers’ Buddhist spiritual practice inspired and guided their application of Soka education. Limitations: The findings are best interpreted within the study’s limitation of selecting participants from a teacher population that would likely perceive Soka education in a largely favorable light. Contribution: Our research poses potential inquiries for further study, given the novelty of the finding that identified how teachers used their Buddhist practice to inspire and advance their teaching. This aspect of teaching practice is not widely represented to date in the Soka education discourse and may have implications for future investigation.